Alkaloids from Cryptocarya densiflora Blume (Lauraceae) and their cholinesterase inhibitory activity. (September 2017) - Wan Othman, Wan Nurul Nazneem; Sivasothy, Yasodha; Liew, Sook Yee; Mohamad, Jamaludin; Nafiah, Mohd Azlan; Ahmad, Kartini; Litaudon, Marc; Awang, Khalijah
Graphical abstract: Highlights: Alkaloidal content of the leaves of Cryptocarya densiflora Blume was investigated. (−)-Desmethylsecoantofine N -oxide (1 ) was a new seco -phenanthroindolizidine alkaloid. Prodensiflorins A and B (2 –3 ) were two new proaporphine alkaloids. Compounds1 –3 were moderate to weak AChE and BChE inhibitors. Compound10 was a DPPH free radical scavenger. Abstract: (−)-Desmethylsecoantofine N -oxide (1 ), a new seco -phenanthroindolizidine alkaloid along with prodensiflorins A and B (2-3 ), two new proaporphine alkaloids, were isolated from the leaves of Cryptocarya densiflora Blume. Their structures were established on the basis of 1D and 2D NMR techniques and LCMS-IT-TOF analysis. (+)- N -methyllaurotetanine (4 ), (+)-laurotetanine (5 ), (+)-nornantenine (6 ), crychine (7 ), (−)-isocaryachine (8 ), (+)-reticuline (9 ), (−)-desmethylsecoantofine (10 ), (+)-oridine (11 ), dicentrinone (12 ) and (−)-antofine (13 ) were also isolated with compounds4, 7 –9 and12–13 being characterized for the first time in this plant. Compounds1 -3 were moderate to weak AChE and BChE inhibitors while compound10 was a DPPH free radical scavenger.